The Transformation of the National Security Paradigm in Indonesia's Border Regions: From a Militaristic Approach to Human Security - Yulius Ida Bagus Suselo; Bambang Kustiawan; Guntur Eko Saputro (UNIVERSITAS PAKUAN, 2026)
This research examines the paradigm shift in Indonesia's national security within border regions, moving from a traditional militaristic focus toward a more holistic human security approach. The analysis was conducted using qualitative methods, policy reviews, and case studies from December 2025 to February 2026. The findings highlight the limitations of conventional military strategies in addressing non-traditional threats, such as illegal trafficking, socio-economic inequality, and community vulnerability. Recent initiatives—most notably the Motaain Border Expo 2025 (a strategic event organized by the National Agency for Border Management (BNPP) through the Motaain Integrated Border Post (PLBN) on December 16–17, 2025, in Belu Regency, East Nusa Tenggara)—along with integrated services at border posts, serve as primary examples of a human-centric security approach that fosters local welfare and cross-border cooperation. This study proposes an integrative model that synergizes securitization with human security, emphasizing both territorial protection and community empowerment. The results suggest that a multidimensional security policy, supported by measurable social and economic indicators, significantly strengthens border stability and resilience. This framework provides a strategic roadmap for policymakers in designing sustainable national security strategies. Keywords: National Security, Human Security, Border Policy, Indonesia, Securitization, Community Empowerment.